The right to paid annual leave as an EU fundamental social right. Comment on Bauer et al.: Joined Cases C-569/16 and C-570/16 Stadt Wuppertal v. Maria Elisabeth Bauer and Volker Willmeroth v. Martina Broßonn, EU:C:2018:871. Issue 3 (June 2019) - Panascì, Maria Antonia
This case note examines the judgment of Court of Justice of the European Union delivered in Joined Cases C-569/16 and C-570/16 Stadt Wuppertal v. Maria Elisabeth Bauer and Volker Willmeroth v. Martina Broßonn on 6 November 2018. It engages with the noteworthy aspects of the ruling, such as the horizontal direct effect of the Charter of Fundamental Rights of the European Union (the Charter), the relationship between primary and secondary law in the European Union legal order and the scope of application of the Charter.